Impact and consequences of Covid-19 on the functioning of minority institutions of the Slovene national community in Austria - Grafenauer, Danijel (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2020)
Crucial for the development and survival of minorities and persons belonging to them is that their situation and position are taken into account in the countries' measures and policies and are not aggravated thereby. This is particularly relevant in times of crisis, such as the Covid-19 pandemic. Social interaction within the minority and the active contact of a national community with its kin-state - currently limited as a result of the measures to contain the coronavirus - are of the utmost importance for all minority national communities. Thanks to its organisational capacity, the Slovene national community in Austria was able to properly respond and adjust to the restrictions imposed, but the cancellation of traditional events and closure of bilingual schools raise questions among the community as to how its identity will survive if it cannot be expressed. There is concern that these consequences, especially since the epidemic continues unabated in the second wave, are likely to have a long-term impact on ethnic vitality.
Keywords: Avstrija; čezmejno sodelovanje; koroški Slovenci; pandemija covid 19; slovenska manjšina; slovenske organizacije v zamejstvu